Soil classification and 1D seismic site response analysis for some areas in Hanoi city - Giang, Kien Trung (H. : ĐHQGHN, 2018)
Along with the development of urban and modern life, Hanoi Capital has been constructing more and more sky buildings, big bridges and huge underground constructions. According to historical studies, Hanoi is a region located on the weak soil ground which has a rather thick sedimentary layer, complicated geology structure and shallow ground water aged in the Holocene and Pleistocene. Hanoi city is cut through by a Red River fault which has been considered to be a strong active fault zone. As a consequence, it is able to cause earthquakes with magnitude M = 6.8 corresponding to the 7th ground vibration level in intensity. In order to predict the casualty of this severe earthquake being able to happen, it is surely essential to assess both seismic site response and geological conditions in Hanoi. In the paper, we will analyze the soil ground data and borehole data obtained in this region to find the specific geological factors which are put into the DeepSoil Program to evaluate local site effects.